Concept of an integrated mobile application aiding electromobility - Csiszár, Csaba; Pauer, Gábor (Transport, 2019)
Increasing acceptance of electromobility is an important step towards sustainable transportation. However, besides its obvious environmental and economic benefits, the technology of Electric Vehicles (EVs) still has some significant operational drawbacks (e.g. relatively short driving range, long recharging time). Advanced mobile applications supporting travellers’ decisions, improving predictability and reliability could play a key role in the promotion of a more widespread use of the technology. Mobile applications can serve as a “platform” between the human component and the integrated system. The aim of our research was to reveal the correspondences between functions, data groups and system components, to create the concept of a complex, integrated information application and to elaborate its innovative functions. As a result of our systematic analysis of the most important, currently available applications, it has been found that important, customizable functions (e.g. charger-point reservation, energy-efficient routing etc.) are not yet available, thus our innovation focused on these information management features. Based on our concept, integrated information applications can be developed, providing real-time personalized service for the users and including all functions related to electromobility.